1. 5x^2=5
divide both sides by 5, x^2 = 1, take the square root of each side. Square root of 1 is 1, or -1. So, x = (1, -1)
2. (x-2)(x-3) = 6
Use FOIL. x^2 - 2x - 3x + 6 = 6, x^2 -5x +6 = 6, subtract 6 from each side, x^2 -5x = 0.
Use quadratic equation x = [-b +- sqr root(b^2 - 4ac)] / 2a. In this case a = 1, b = -5, c = 0
[-(-5) +- sqr root(-5^2 - 4(1)(0))] / 2(1)
[5 +- sqr root (25)] / 2
[5 +- 5] / 2
[5 + 5] / 2 = 5; [5 - 5] / 2 = 0
x = (5, 0);
QED
2007-07-17 08:30:56
·
answer #1
·
answered by Dave S. 2
·
0⤊
0⤋
Dividing both sides of 5x^2=5 by 5 gives x^2 = 1, so x = 1 or -1.
For the second one, although it's already factored on the left, you'll have to expand and recombine the terms:
x^2 - 5x + 6 = 6
x^2 - 5x = 0
x(x-5) = 0
So x = 0 or 5.
2007-07-17 15:23:44
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
5x^2=5, first divide both sides by 5: x^2=1 now take the square root to learn that x can = + or -1 (the square of a neg. number is a positive)
(x-2)(x-3)=6 first expand to get x^2-5x+6=6, subtract 6 from each side to get x^2-5X=0 it should be obvious that x=0
2007-07-17 15:27:22
·
answer #3
·
answered by cvtman2003 2
·
0⤊
0⤋
5x^2 = 5 or x^2 = 1, so x = +/1
x^2 -5x + 6 = 6, then
x^2 - 5x = 0, or x^2 = 5x
One solution is x = 0.
Divide by x (not = 0), and get x = 5, so x = 0, 5.
2007-07-17 15:26:11
·
answer #4
·
answered by John V 6
·
0⤊
0⤋
5x^2 = 5
divide both sides by 5:
x^2 = 1
whenever you have something ^2, take the square root of it to simplify:
sqrt(x^2) = sqrt(1)
which is:
x = sqrt(1).
2nd one:
multiply out:
x^2 - 5x + 6 = 6
combine like terms:
x^2 - 5x = 0
x(x-5)=0
x = 0 or 5
2007-07-17 15:25:21
·
answer #5
·
answered by miggitymaggz 5
·
0⤊
0⤋
i think it want's you to solve for x. so it's asking you 5 multiplied by what squared will give you 5. the answer would be 1. for the first question. because 1^2 is 1. and 5*1 is 5.
the second question is asking what -2 * that same number -3 give you six. the answer is 5. because 5-2=3, and 5-3=2. and 3*2=6.
2007-07-17 15:25:18
·
answer #6
·
answered by rufsketch1 3
·
0⤊
0⤋
Question 1
5x² = 5
x² = 1
x = ± 1
Question 2
x² - 5x + 6 = 6
x² - 5x = 0
x (x - 5) = 0
x = 0 , x = 5
2007-07-20 17:47:34
·
answer #7
·
answered by Como 7
·
0⤊
0⤋
5x^2=5
so x^2=5/5=1
so x=+-1 ans
(x-2)(x-3)=6
so x^2-2x-3x+6=6
or x^2-5x=0
or x(x-5)=0
so Either x=0 Or x=5 ans
2007-07-17 15:42:47
·
answer #8
·
answered by MAHAANIM07 4
·
0⤊
0⤋
5x^2=5
x=1
take 5 from LHS divide by RAHS - gives you one. square root of 1 is one.
(x-2)(x-3)
x^2-3x-2x+6=6
x(x-5)=0
roots are 0 and 5
use FOIL method and ta-da!
2007-07-17 15:23:43
·
answer #9
·
answered by Anonymous
·
0⤊
1⤋